English, Islam, and Secular values in Pre-service English Teacher Education: Exploring the Curricular Balance - Hadi, Abdul (Proceeding of International Conference on Teacher Training and Education, 2016)
Over the past few decades, Pre-service English Teacher Education (PETE) Programs have been offered in Indonesian Islamic state universities, which traditionally only provide education programs in Islamic studies. This new development became particularly evident after the transformation of several former state institutes and schools for Islamic studies into state Islamic universities. This transformation calls for an understanding of how English, Islam, and secular values are integrated into a balanced proportion in a PETE Programâs curriculum. This paper draws on findings from a case study exploring the interplay among English, Islam, and secular values in principles, content, and implementation of PETE curriculum in an Islamic state university. The findings showed that the principles underpinning PETE curriculum in the university reflect a balanced curricular representation of English, Islam, and secular values in the following terms: (1) studentsâ and lecturersâ roles in learning process, (2) theories and practice, and (3) institutional identities and professional realities. Similarly, a balanced proportion of English, Islam, and secular values was found in the curriculum content. This balanced proportion of curriculum content was reflected in (1) components of the curriculum content (language component, educational and pedagogical component, institutional component) and (2) pedagogical characteristics connecting the curriculum content (Islamic, integrated, theoretical, practical, contextual). However, the study revealed that there was inadequacy of balance in the curricular accommodation of English, Islam, and secular valuesâa finding that was represented by curriculum implementation that was fragmented, inadequately practical, and inadequately contextual. The above findings will be discussed based on perspectives from theoretical and empirical literature in second language and general teacher education, Indonesian education, and Islamization and secularization of education. The presentation will conclude with some curriculum and policy recommendations for sustainable 21st century Pre-service English Teacher Education in Indonesian state Islamic universities or in other similar contexts.